PERANAN BIROKRASI PEMERINTAH TERHADAP KINERJA APARATUR SATUAN POLISI PAMONG PRAJA KABUPATEN SIDENRENG RAPPANG - Hendra Anda (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2018)
The results showed that the role of the government bureaucracy on the performance of the Civil Service Police Unit of Sidenreng Rappang Regency had been carried out well 65.18% seen from the indicators of division of labor, discipline and supervision, a systematic system of rules, positions following the principle of hierarchy, officials bound to one formal task. , technical requirements and positions are low-quality careers because they are not in accordance with the field and work he is doing, while judging from the performance of the service apparatus, 67.75% are carried out with indicators of loyalty, work performance, discipline, cooperation, skills and responsibilities while the factors that influence the role of the government bureaucracy on the performance of the Civil Service Police Unit apparatus of Sidenreng Rappang Regency are bureaucratic reform efforts that have been carried out at the Civil Service Police Unit Office of Sidenreng Rappang Regency are not good 48.67% seen from the quality of work indicators n, Quantity of work and timeliness.